2014
DOI: 10.1111/jne.12170
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Insulin‐Induced Hypoglycaemia on the Peripheral Nervous System: Focus on Adaptive Mechanisms, Pathogenesis and Histopathological Changes

Abstract: ).Insulin-induced hypoglycaemia (IIH) is a common acute side effect in type 1 and type 2 diabetic patients, especially during intensive insulin therapy. The peripheral nervous system (PNS) depends on glucose as its primary energy source during normoglycaemia and, consequently, it may be particularly susceptible to IIH damage. Possible mechanisms for adaption of the PNS to IIH include increased glucose uptake, utilisation of alternative energy substrates and the use of Schwann cell glycogen as a local glucose r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

7
39
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(46 citation statements)
references
References 135 publications
(203 reference statements)
7
39
0
Order By: Relevance
“…Males received higher doses than females, which is most likely the cause of the increases counter-regulation compared to females; however, a direct damaging effect of insulin on the peripheral nerves should also be considered. As previously discussed in detail, insulin acts as a neuronal growth factor and serves as a promoter of axonal regeneration after injury of peripheral nerves [13]; therefore, it is unlikely that hyperinsulinaemia would give rise to axonal degeneration. Most likely the hypoglycaemia caused the nerve changes, which in turn gave rise to the muscle changes [13].…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…Males received higher doses than females, which is most likely the cause of the increases counter-regulation compared to females; however, a direct damaging effect of insulin on the peripheral nerves should also be considered. As previously discussed in detail, insulin acts as a neuronal growth factor and serves as a promoter of axonal regeneration after injury of peripheral nerves [13]; therefore, it is unlikely that hyperinsulinaemia would give rise to axonal degeneration. Most likely the hypoglycaemia caused the nerve changes, which in turn gave rise to the muscle changes [13].…”
Section: Discussionmentioning
confidence: 90%
“…As previously discussed in detail, insulin acts as a neuronal growth factor and serves as a promoter of axonal regeneration after injury of peripheral nerves [13]; therefore, it is unlikely that hyperinsulinaemia would give rise to axonal degeneration. Most likely the hypoglycaemia caused the nerve changes, which in turn gave rise to the muscle changes [13]. This is also supported by a study in which normoinsulinaemic hypoglycaemic rats displayed peripheral neuropathy, while animals with hyperinsulinaemic normoglycaemia did not [14].…”
Section: Discussionmentioning
confidence: 90%
“…It has been suggested but not yet clarified that skeletal muscle myopathy seen during IIH is secondary to the peripheral neuropathy caused by partial denervation of the myofibres . Therefore, one of the aims of the present study was to investigate progression and sequence of myopathy in skeletal muscle tissue of the thigh in relation to neuropathy in sciatic nerves.…”
Section: Discussionmentioning
confidence: 95%
“…Peripheral nerves rely on glucose as their primary source of energy, a dependency that probably contributes to the susceptibility towards IIH-induced injury [9,12]. It has been shown that changes caused by IIH in mice and rats may include axonal degeneration in peripheral nerves [9,[13][14][15][16][17][18].…”
mentioning
confidence: 99%
See 1 more Smart Citation